ANTIDIABETIC EFFECT EVALUATION AND CHARACTERIZATION OF BIOACTIVE COMPOUNDS ISOLATED FROM HYDROLEA ZEYLANICA - Borkar Vijay S; Senthil Kumaran K; Senthil Kumar KL; Gangurde Hemant H; Chordiya Mayur A (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
The whole plant of Hydrolea zeylanica (HZ) (Hydrophyllaceae family) was coarsely powdered and extracted with ethanol using soxhlet apparatus. The ethanol extract was then fractionated successively using various polarity ranges of solvents and screened for in-vivo antidiabetic activity using streptozotocin induced diabetic male wistar rats. The phytochemical investigation of all the fractions and powdered drug analysis was performed. Among the fractions evaluated, chloroform fraction showed highest decrease in blood glucose, total cholesterol and serum triglyceride level as 75.11%, 59.77% and 35.98% respectively when treated at 50 mg/mL concentration. As the chloroform fraction has shown better potency towards antidiabetic activity, was subjected to chromatographic separation and three compounds stigmasterol, kaempferol and p- coumaric acid were isolated and characterized by various spectroscopic techniques. The overall results tend to suggest the antidiabetic activity of HZ and principal source of presumed bioactive compounds which may be responsible for many of the pharmacological properties.Key word: Hydrolea zeylanica, antidiabetic, total cholesterol, triglycerides, in vivo.